2004
DOI: 10.1063/1.1806253
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of correlated diffusion of Si and B in thermally grown SiO2

Abstract: Simultaneous diffusion of Si and B in thermally grown SiO 2 is modeled taking into account the effect of SiO molecules generated at the Si/ SiO 2 interface and diffusing into SiO 2 to enhance both Si and B diffusion. Based on the model, we simulated experimental profiles of coimplanted 30 Si and B in 28 SiO 2 , which showed increasing diffusivities with decreasing distance from the interface. The simulation results show that the SiO diffusion is so slow that the SiO concentration at the near-surface region cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Recently, we have shown that SiO molecules, which are important diffusing species in SiO 2 , enhance both Si self-diffusion and B diffusion in SiO 2 . 7,8) This leads us to assume that the incorporation of N reduces the SiO diffusivity in SiO 2 because the existence of N retards B diffusion, which is enhanced by SiO. This assumption is also consistent with the increase of SiO 2 viscosity with N incorporation because diffusion of SiO is closely related to the viscosity of SiO 2 and viscosity is inversely proportional to diffusivity.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Recently, we have shown that SiO molecules, which are important diffusing species in SiO 2 , enhance both Si self-diffusion and B diffusion in SiO 2 . 7,8) This leads us to assume that the incorporation of N reduces the SiO diffusivity in SiO 2 because the existence of N retards B diffusion, which is enhanced by SiO. This assumption is also consistent with the increase of SiO 2 viscosity with N incorporation because diffusion of SiO is closely related to the viscosity of SiO 2 and viscosity is inversely proportional to diffusivity.…”
Section: Introductionsupporting
confidence: 64%
“…The assumption that the SiO diffusivity exponentially decreases with increasing N concentration was introduced in analogy with B diffusivity in SiO 2 , which exponentially increases with B concentration. 7,8) During oxynitridation, the SiO diffusion is strongly retarded by the N at the interface. This retardation increases the SiO concentration in SiO 2 near the interface as oxynitridation proceeds, which decreases the oxynitridation rate with time.…”
Section: Interfacial Si Emission Model For Oxynitridationmentioning
confidence: 99%
“…Figure 3 shows the experimental B profiles in lowdose samples with various thicknesses after annealing at 1250°C for 6 h. In the same way as Si self-diffusion, the B diffusion shows a clear dependence on the thickness of the 28 SiO 2 layer; the shorter the distance from the Si-SiO 2 interface, the higher the B diffusivity in SiO 2 . [15,16] This tendency was also observed for the high-dose samples and other temperatures used in this study. The distance dependence of B diffusivity indicates that the SiO molecules, which are generated at the Si-SiO 2 interface and diffusing into SiO 2 , enhance not only Si self-diffusion but also B diffusion.…”
Section: B Diffusionsupporting
confidence: 78%
“…The profile of 30 Si in the high-dose samples shows larger diffusion than that without B. [15,16] On the other hand, the 30 Si profile of the low-dose samples (not shown in Fig. 4) showed no significant difference from that without B.…”
Section: Basic and Applied Research: Section Imentioning
confidence: 86%
“…We have studied the transport of Si during the thermal oxidation experimentally as well as theoretically. Experiments based on isotope technology have revealed that some Si-related species diffuse from the interface and enhance the diffusion in the oxide (28,29,31,32,36,47,48). These experimental results indicate that the transport of Si is a very important consideration in the thermal oxidation process, while the microscopic picture for the Si-related species is not well clarified yet.…”
Section: Transport Of Simentioning
confidence: 99%